Incidence rate and spatial clustering of measles cases in Malaysia, 2018–2022 - Mat Daud, Mohd Rujhan Hadfi; Yaacob, Nor Azwany; Arifin, Wan Nor; Md Sani, Jamiatul Aida; Wan Ibadullah, Wan Abdul Hannan (International Journal of Public Health Science (IJPHS), 2025)
The distribution of measles varies worldwide. Malaysia has seen fluctuating incidence rates of measles across its districts, highlighting the persistent challenge of measles control despite national vaccination efforts. This study aimed to map the incidence rates of measles and identify hotspots areas of measles in Malaysia between 2018 and 2022. The study utilized secondary data from the Disease Control Division, Ministry of Health Malaysia, and was analyzed through spatial autocorrelation techniques. Choropleth map applied to the incidence rate of measles and Global Moran’s I statistics quantified spatial autocorrelation, supplemented by local indicators of spatial association (LISA) for localized analysis. The measles incidence rate exceeded 500 per million population in Bintulu, Marudi, and Miri, Sarawak in 2018 and in Gua Musang, Kelantan in 2019. There is a downward trend in the incidence rate across the districts in Malaysia. The Global Moran’s I statistic revealed significant positive spatial autocorrelation of measles cases in Malaysia from 2018 to 2022. Districts, specifically in Klang Valley, have been identified as persistent hotspot areas. There is a need for continuous surveillance, adequate vaccination coverage, and supplementary public health measures, especially in identified hotspot areas, in order to achieve measles elimination goals in Malaysia.